In the inland sea of Ultima Esperanza: Dynamics of occupation and canoeing mobility in Diego Portales Island (Magallanes, Chile) - Garcia-Piquer, Alberto; Navarrete, Vanessa; Aguilera, Nelson; Carracedo, Robert; Franch, Anna; Garcia, Christian P.; Ros-Sabe, Eva; Zegers, Gabriel; Prieto, Alfredo; Pique, Raquel (My University, 2022)
Characterizing hunter-fisher-gatherer mobility strategies in island and coastal environments is key to understanding past human-environment interaction. Seafaring communities inhabiting the inland sea of Ultima Esperanza (Magallanes, Chile) maintained a subsistence strategy focused on hunting, gathering, and fishing until the beginning of the twentieth century. In this work we present the new archaeological findings from Diego Portales island (Almirante Montt Gulf) and discuss subsistence and mobility strategies in the context of the regional archaeological record. The systematic survey of the northeast tip of the island allowed us to record eight archaeological shell midden sites, on both the east and west coasts. Site location was determined by geotopographic factors. The excavation of two of the sites, Bahia Easter 1 and Bahia Easter 2, has provided evidence of occupation dating to the Final Late Holocene and covering a time span of almost 2,000 years. These two sites are associated with hunter-fisher-gatherer seafaring peoples who repeatedly frequented the area. Archaeozoological and archaeobotanical studies suggest a subsistence strategy based on the exploitation of at least a dozen different species of marine and terrestrial resources. Among the latter, the archaeological remains of huemul (Hippocamelus bisulcus) are particularly abundant. These mid-sized deer were probably hunted at the Patagonian coast and transported to the island. The location of the island, in a transit area between the external channels and the inland sea, and between the northern archipelagos and the continent, together with resource abundance and diversity, suggest that Diego Portales was a privileged area for seafaring occupation, especially in spring and summer.
Keywords: hunter-fisher-gatherers; patagonia; south america; late holocene; mobility strategies; coastal environments